The visual preacher : proclaiming an embodied word - Thomason, Steve (Working preacher books., 2022)
In The Visual Preacher: Proclaiming an Embodied Word, Steve Thomason's winsomely illustrated text shows preachers basic principles and visual techniques to create and use images that will make them even more effective communicators than they already are. Preachers need not be skilled artists or technological wizards to apply Thomason's ideas.